Visual field - Sidlová, Jana Sokolová; Benes, Pavel; Holoubková, Zuzana (Collegium antropologicum, 2013)
This article is dedicated to main information about visual field, monocular and binocular ranges of visual field including their defects. Visual field loss may occur to disease of the eye, optic nerve or brain. Typical changes are present at glaucoma and macular degeneration. Visual pathway is also mentioned. The basic medical examinations of visual fields are Amsler grid, kinetic and static perimetry and the other. Newer method is microperimetry which detects the changes directly on the retina. The aim of this poster is importance and determination of visual field as a preventive ophthalmologic and optometric examination.
Keywords: Visual Fields; Humans; zraková pole; testy zrakového pole; lidé; Visual Field Tests